2021
DOI: 10.1177/01650254211029715
|View full text |Cite
|
Sign up to set email alerts
|

The relation between defending, (dis)liking, and the classroom bullying norm: A cross-sectional social network approach in late childhood

Abstract: This study investigates the extent to which defending victims of bullying depends on liking and disliking and its relation with the classroom bullying norm (descriptive and popularity) in a sample of 1,272 students (50.8% boys) in 48 fifth-grade classrooms. Social network analysis with bivariate exponential random graph modelings showed that children are more likely to defend victims whom they like, who like them, and who are liked by the same classmates than victims who they dislike, who dislike them, and wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 74 publications
2
16
0
Order By: Relevance
“…Our study findings demonstrated that having friendships and classmates willing to help each other in the class, being fond of spending time together in class, and believing that one is accepted as an individual by classmates are associated with less likelihood for participation in fights multiple times and participation in bullying both once and multiple times. Friendships help students face problems by building their sense of belonging, self-esteem, and social skills [30] and defend them from bullying [31], highlighting the finding in our study that friendship among students in class and willingness to help each other is the predictor for less participation in fights multiple times and participation in bullying at least once. Participating in bullying and fighting affects everyone who is involved and witnesses it.…”
Section: Discussionsupporting
confidence: 73%
“…Our study findings demonstrated that having friendships and classmates willing to help each other in the class, being fond of spending time together in class, and believing that one is accepted as an individual by classmates are associated with less likelihood for participation in fights multiple times and participation in bullying both once and multiple times. Friendships help students face problems by building their sense of belonging, self-esteem, and social skills [30] and defend them from bullying [31], highlighting the finding in our study that friendship among students in class and willingness to help each other is the predictor for less participation in fights multiple times and participation in bullying at least once. Participating in bullying and fighting affects everyone who is involved and witnesses it.…”
Section: Discussionsupporting
confidence: 73%
“…Several experimental studies have shown that students conform to the popularity norm regarding health-risk behavior (Cohen & Prinstein, 2006), alcohol consumption (Teunissen et al, 2012), and prosociality (Choukas-Bradley et al, 2015). Popularity classroom norms are typically operationalized as the within-classroom correlation between a particular behavior and perceived popularity (e.g., Garandeau et al, 2022; Rambaran et al, 2022). An alternative for the correlation-based popularity norm is a prevalence-based popularity norm, where the average behavior of popular classmates is computed (Dijkstra et al, 2008; Menesini et al, 2015; Velásquez et al, 2021), or a network-based weighted norm, referring to a measure that gives more weight to the behavioral scores of students who hold a central position in the classroom network, based on the number of direct and indirect relationships (Jackson et al, 2015).…”
Section: Different Types Of Classroom Normsmentioning
confidence: 99%
“…Where it was argued that peer dynamics and hierarchies might differ across the different school settings, it is not unlikely that also within the same school setting the dynamics might differ, across classrooms, or grades. However, a clear-cut measure of peer hierarchy, dominance or classroom norms is not readily available and is a topic of study on its own (Rambaran, van Duijn, Dijkstra, & Veenstra, 2019b;Salmivalli, 2010).…”
Section: Implications Limitations and Directions For Future Researchmentioning
confidence: 99%